ANALISIS KETERSEDIAAN PELAYANAN FASILITAS SOSIAL EKONOMI DI KECAMATAN POLEANG TIMUR KABUPATEN BOMBANA - Andi Muh. Syaifullah; Ahmad Ahmad; La Ode Syamsul Barani (Universitas Halu Oleo, 2018)
The purpose of this study is to find out the availability of social service facilities (educational facilities and health facilities) and how the availability of economic service facilities. The method used in this research is descriptive research method using a qualitative approach. The technique of data collection is done by the library study method.Based on the results of the study, it is known that: (1) Availability of social facilities in this case the existing educational facilities in the east poleang district for the level of kindergarten and equivalent have been very adequate and are in accordance with national standards, for the elementary and equivalent levels and in accordance with national standards, but for junior and senior high school levels, they are still inadequate and do not meet national standards, while the level of senior high school and equivalent is in line with national standards and the availability of social facilities in this case health facilities quite adequate and can meet the needs of the population in east poleang sub-district. (2) Availability of economic service facilities including market service facilities, shops, kiosks or stalls and east poleang bank facilities are available and sufficient.